Customers experience and problem resolutions in retail banking. Some empirical evidence from Italian banking. (2016) - Malinconico, Antonella; Fuccio, Nathalie
Currently, few studies have investigated how bank-specific determinants affect customer experience in retail banking. The objective of this paper is twofold: to provide a literature review about customer dissatisfaction in retail banking and to shed more light on different behaviours of banks regarding customer complaints. Our hypotheses are tested on a large sample of Italian banks on problem resolutions performance measured from 2012 to 2014, using bank-level balance sheets and appeals to "Arbitro Bancario e Finanziario". We detected differences in the complaints management of different types of banks during turbulent financial market conditions. We compared bank size and bank legal form as possible sources of organisational friction studying their impact on the likelihood of customer dissatisfaction. Our findings highlight that, the small banks and cooperative banks are less inclined to have retail customers with dissatisfaction than large banks and joint-stock banks.